Design and Development of a Mobile Application for Palm Oil Harvest Recording and Reporting Using a User-Centered Design (UCD) - Kisah Tiara Sihombing; Ritna Wahyuni; Ratu Mutiara Siregar (Universitas Malikussaleh, 2026)
The digitization of oil palm harvest recording is necessary to improve data accuracy, reporting efficiency, and operational transparency in plantation environments. The manual recording process currently used often leads to reporting delays, data inconsistencies, and errors in harvest data recording. This study aims to design and develop a mobile application for oil palm harvest recording and reporting using a User-Centered Design (UCD) approach to meet user needs and field conditions. The research methods included observation, interviews, user needs analysis, system design, prototype development, and system evaluation. Functional testing was conducted using black-box testing, while usability testing utilized the System Usability Scale (SUS). The developed application provides features for recording fresh fruit bunches (FFB), loose fruit recording, photo documentation, offline data storage, automatic synchronization, foreman validation, and periodic reporting. The test results indicate that all system features functioned properly and achieved an average SUS score of 77.75, which falls into the “Good” category. These results demonstrate that the application is easy to use and accepted by users. Thus, the User-Centered Design approach successfully produced a practical, efficient, and user-friendly application to support oil palm harvest data management.